DOI: 10.11606/t.3.2010.tde-20082010-154954
|View full text |Cite
|
Sign up to set email alerts
|

Microtubos e nanotubos de silício fabricados por processos químicos e eletroquímicos.

Abstract: Meu maior agradecimento é para meu fiel amigo e companheiro: O senhor Jesus, que andou e continua a andar junto comigo no dia-a-dia da minha vida, com sua santa presença, dando-me forças na luta diária e permaneceu sempre junto à mim tanto nos momentos difíceis quanto nos momentos de alegria.Obrigado meu Deus pela tua amizade e cuidado desinteressado.Meu eterno agradecimento para o amor da minha vida, minha amiga, companheira e amante esposa Ana Maria Sullca Farfán pela sua dedicação, paciência e amor, que me … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 106 publications
(332 reference statements)
0
4
0
Order By: Relevance
“…This last condition of the SCR layer is perhaps more important than the barrier since Zhang and Lehmann reported that in fluoride media, the silicon is predominantly dissolved by an electrochemistry route by hole consumption from silicon substrate . Therefore, the different silicon dissolution rate in the porous silicon layer leads to nanotubes formation . The tube formation starts with silicon dissolution from the D region (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This last condition of the SCR layer is perhaps more important than the barrier since Zhang and Lehmann reported that in fluoride media, the silicon is predominantly dissolved by an electrochemistry route by hole consumption from silicon substrate . Therefore, the different silicon dissolution rate in the porous silicon layer leads to nanotubes formation . The tube formation starts with silicon dissolution from the D region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This mixture solution was also used for porous metal synthesis and silicon microtube fabrication using a porous silicon layer as a sacrificial substrate . The pH level of the mixture solution and the dopant level of silicon are the determinant conditions in order to obtain one or the other structure . The best pH level of the solution for silicon microtubes formation was 6.5 because at a lower level of pH the structure was needle‐like and when the pH level is increased to 7.5, Ni microtubes were formed .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations